Pengaruh Penyaluran Dana Zakat, Infaq, Sedekah (ZIS) dan Inflasi terhadap Pertumbuhan Ekonomi di Kalimantan Selatan pada Periode 2011-2020 - Kurniawan, Teguh; Maulina, Dessy (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
This study expects to investigate the effect of ZIS reserves and expansion on monetary development in South Kalimantan from 2011 to 2020. The strategies utilized in this examination incorporate quantitative techniques, and the method used differs from direct relapse. The information used in this study is optional information taken by the dissemination of ZIS assets as indicated by BAZNAZ of South Kalimantan Province (Badan Amil Zakat of South Kalimantan Province) and expansion rates taken by BPS Kalsel (Central Bureau of Statistics) in South Kalimantan 2011-2020 which incorporates information South Kalimantan's yearly expansion. The outcomes as per the review got a result which showed that the ZIS reserve circulation variable (X1) altogether affected financial development in South Kalimantan, and the expansion variable (X2) showed that it affected monetary development in South Kalimantan Province and the variable dissemination of assets. ZIS and expansion simultaneously fundamentally affected economic growth in South Kalimantan from 2011 to 2020.